Efektivitas Kepemimpinan Kepala Sekolah Dalam Upaya Optimalisasi Pembelajaran Jarak Jauh di Taman Kanak-Kanak Kecamatan Mapanget Kota Manado - Fera Luicia Tampi (Peneliti.net, 2022)
This research was conducted with the aim of analyzing and describing the effectiveness of the principal's leadership, the teacher's perspective on the principal's leadership behavior, and the parents' perspective on the effectiveness of the principal's leadership in Kindergarten in Mapanget District, Manado City. Referring to the nature of the problem and research objectives, it seems that the research is of a qualitative nature, so that the relevant methods used are qualitative and naturalistic methods. Data collection techniques used in this research are observation, interviews, and documentation studies. The data analysis technique used in this research is descriptive qualitative analysis. The data analysis process in this study uses the Miles model interactive analysis process, namely data reduction, data collection, data presentation, and drawing conclusions. Based on the results of this observation and research, children are very interested in participating in (permanent) learning by optimizing distance learning. It can be seen in this study that the optimization of distance learning has very well developed criteria with an average presentation of 83.77%. Based on the results of the research and discussion, it can be concluded that the principal's leadership in efforts to optimize distance learning in kindergarten still needs to be improved so that distance learning becomes more effective and fun.